Cele tymczasowego aresztowania a powszechność jego stosowania w praktyce sądów polskich - Kalisz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article analyses the aims of application and implementation of temporary arrest and it focuses mainly on normative issues. The presentation of data concerning the application of temporary arrest in Poland since 1999 until the present time is an important supplementation of the theoretical deliberation. Reflecting upon the data analysis, one may say that Poland is one of the European countries which rarely apply temporary arrest. This thesis contradicts the common opinion that temporary arrest is overused in Poland.
Keywords: system więziennictwa; areszt prewencyjny; populacja osadzonych